Laser driven melt pool resonances through dynamically oscillating energy inputs - Rupp, Marco; Schwarzkopf, Karen; Döring, Markus; Hayashi, Shuichiro; Schmidt, Michael; Arnold, Craig B. (Journal of Manufacturing Processes, 2024)
Spatially selective melting of metal materials by laser irradiation allows for the precise welding as well as the 3D printing of complex metal parts. However, the simple scanning of a conventional Gaussian beam typically results in a melt track with randomly distributed surface features due to the complex and dynamic behavior of the melt pool. In this study, the implications of utilizing a dynamically oscillating energy input on driving melt track fluctuations is investigated. Specifically, the laser intensity and/or intensity distribution is sinusoidally modulated at different scan speeds, and the effect of modulation frequency on the resulting surface features of the melt track is examined. The formation of periodically oriented surface features indicates an evident frequency coupling between the melt pool and the modulation frequency. Moreover, such a frequency coupling becomes most prominent under a specific modulation frequency, suggesting resonant behavior. The insights provided in this study will enable the development of novel methods, allowing for the control and/or mitigation of inherent fluctuations in the melt pool through laser-driven resonances.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Dynamic energy modulation; Frequency coupling; Laser driven resonance; Laser melting